E-book development of group guidance model with use-bases sociodrama technique in improving self-resilience of students victims of bullying - Mahmud, Firman; Zakaria, Noor Syamilah; Ramdani; Susanto, Eko; Fitriana; Hariko, Rezki (Society of History and Cultural Studies, 2024)
Bullying is a terrifying phenomenon for individuals who experience it, therefore victims of bullying need resilience to deal with bullying situations that occur. This study aims to analyze the development of a group counseling e-book model with user web-based sociodrama techniques to increase the resilience of bullied students.The research used quantitative and qualitative methods with Research and Development (R&D). The subjects of this study were 10 students who were victims of bullying for the experimental group at SMA N 15 Padang. Data were collected through observations, interviews, documents, and research tools on self-healing. Data were analyzed using the Wilcoxon Signed Rank Test and SPSS version 21.00. The results show that (1) the group counseling e-book with social learning techniques based on the user's website is considered feasible for teachers/counselors to use to increase students' self-recovery ability. students who are victims of bullying, (2) the group's level of use of instructional eBooks with socio-dramatic techniques considered very good for use in guidance and counseling services. Therefore, it can be seen that the prototype of a group counseling e-book with web-based socio-dramatic techniques aimed at enhancing the self-resilience of bullied students is considered feasible and can be taught. used by the counselor/counselor to increase self-healing ability resilience of students who are victims of bullying.